IMIDACLOPRID INDUCED INTOXICATION IN SOIL ISOLATE BREVUNDIMONAS SP. MJ 15: Life Science-Microbiology - A. A. SHETTI; B. B. KALIWAL (International Journal of Life Science and Pharma Research, 2012)
Imidacloprid (I-[(6-chloro-3-pyridinyl)-methyl]-N-nitro-2-imidazolidinimine), is a chloronicotinyl insecticide and it is used to control biting and sucking insects. In India it is used for variety of crops. Present investigation was carried out to study the effect of imidacloprid on bacterial populations in soil and further to elucidate its toxic effect on growth and biochemical parameters of soil isolate Brevundimonas sp. MJ15. The laboratory and field studies were conducted to determine the effects of imidacloprid on soil bacterial populations. For Laboratory studies the concentrations 125, 250, 500, and 1000 ppm of imidacloprid was applied and field studies involved application of imidacloprid at recommended rates and at 1.5x rate. Toxic effect on bacteria was evaluated at 0, 7, 14, 21 and 28 days after treatment with imidacloprid. The bacterial population was estimated using the standard dilution plate technique. Results obtained from both studies revealed that imidacloprid caused significant (P<0.05) reduction in bacterial population in the soil. However, in the field studies toxic effect disappeared after 28 days of application. The study involving soil isolate Brevundimonas sp. MJ15 with molar concentrations of 10-3 to 10-7 of insecticide showed there was significant increase in percent inhibition of DNA, RNA, protein and glucose. The inhibitory effect increased with the concentration of insecticide proving that the inhibitory effect is dose dependent. There was significant (P<0.05) decrease in the growth on treatment with various molar concentrations of insecticide when compared to that of control and effect was dose dependent. The present investigation proves that imidacloprid has toxic effect on bacterial populations in soil and this effect is dose dependent. Study also showed that imidacloprid affects the biochemical contents and intern growth of soil isolate Brevundimonas sp. MJ15.